2003
DOI: 10.1023/a:1025437115182
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of perillyl alcohol (NSC 641066) administered daily in patients with metastatic androgen independent prostate cancer

Abstract: Perillyl alcohol administered at this dose and formulation did not have any objective clinical activity in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…(Lamiaceae) which has been used for treating colds, food allergy, and depression [ 141 , 142 ]. Considering the absence of ICL1 in human, the well-tolerated profile in human, and the fact that Phase II trials have been conducted in patients with cancers, perillyl alcohol might serve as an interesting candidate for antifungal therapies against C. albicans [ 143 , 144 ].…”
Section: Virulence Factorsmentioning
confidence: 99%
“…(Lamiaceae) which has been used for treating colds, food allergy, and depression [ 141 , 142 ]. Considering the absence of ICL1 in human, the well-tolerated profile in human, and the fact that Phase II trials have been conducted in patients with cancers, perillyl alcohol might serve as an interesting candidate for antifungal therapies against C. albicans [ 143 , 144 ].…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Based on the collective outcome of the above-mentioned animal studies, POH was formulated in soft gelatin capsules and tested in a number of phase I and II cancer trials, where it was given orally three to four times each day for several months [ 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. However, the results were disappointing.…”
Section: Intranasal Drug Deliverymentioning
confidence: 99%
“…d-Limonene and perillyl alcohol suppressed the incorporation of radiolabeled mevalonate into small G-proteins and this action has been attributed to the inhibition of farnesyl protein transferase activity [35]. Phase I studies of d-limonene [36], and phase I [37] and II [38] studies of perillyl alcohol revealed dose-limiting toxicities, such as nausea, vomiting, anorexia, and eructation. The monoterpenoids carveol, uroterpenol, and sobrerol have demonstrated chemopreventive activity against mammary cancer in rats when fed during the initiation phase [39].…”
Section: Monoterpenesmentioning
confidence: 99%